2009
DOI: 10.1002/jhm.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a subcutaneous insulin protocol, clinical education, and computerized order set on the quality of inpatient management of hyperglycemia: Results of a clinical trial

Abstract: BACKGROUND:Inpatient hyperglycemia is associated with poor patient outcomes. It is unknown how best to implement glycemic management strategies in the non–intensive care unit (ICU) setting.OBJECTIVE:To determine the effects of a multifaceted quality improvement intervention on the management of medical inpatients with diabetes mellitus or hyperglycemia.DESIGN:Before‐after trial.SETTING:Geographically localized general medical service staffed by physician's assistants (PAs) and hospitalists.PATIENTS:Consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 24 publications
(30 reference statements)
2
86
0
4
Order By: Relevance
“…23 Studies by others have shown that a combination of structured insulin orders combined with staff education to partially alleviates clinical inertia in the hospital. [24][25][26][27][28][29] Our facility implemented computerized order entry in 2007 that includes provisions to order basal, prandial, and correction insulin treatment that are accessible to all practitioners. However, despite all these efforts at our institution, clinical inertia remains evident among the inpatient surgical practices.…”
Section: Discussionmentioning
confidence: 99%
“…23 Studies by others have shown that a combination of structured insulin orders combined with staff education to partially alleviates clinical inertia in the hospital. [24][25][26][27][28][29] Our facility implemented computerized order entry in 2007 that includes provisions to order basal, prandial, and correction insulin treatment that are accessible to all practitioners. However, despite all these efforts at our institution, clinical inertia remains evident among the inpatient surgical practices.…”
Section: Discussionmentioning
confidence: 99%
“…Possible electronic implementation approaches are validated alerts and guidelines on the prescription of antidiabetic medication, especially insulin. 1,19,[27][28][29] In summary, our results show insufficient control of hyperglycemia in noncritically ill hospitalized patients with diabetes despite considerable glycemic management efforts. While the data indicate substantial glycemic management effort in the care of diabetes patients, it did not result in appropriate glycemic control according to recent guidelines.…”
Section: Discussionmentioning
confidence: 77%
“…One study 40 showed incremental benefits in BG control after switching from SSI to an insulin management algorithm, with a significant decrease in the amount of time BG was uncontrolled (BG4180 mg/ dL; 30% down from 38%, p50.005). The second study 62 showed a clear improvement in outcomes with a 10% improvement in patients achieving BG between 160 and 180 mg/dL, a 23% decrease in length of stay (112 vs. 86 h), and a decreased need for supplemental insulin (8% of patients down from 29%). Neither study aggressively titrated to low BG targets, thereby avoiding hypoglycemia, but both studies required tightly scheduled BG monitoring and insulin delivery, and strict algorithms for lowering BG.…”
Section: Insulin Therapy In Non-critically Ill Patientsmentioning
confidence: 91%